The Relationship Between Job Satisfaction And Organizational Commitment On Turnover Intentions - Mohamed, Waled A. (2008)
The purpose of this study is to investigate whether there is any relationship between job satisfaction, organizational commitment and turnover intentions. The survey method was employ with the quantitative data were processed using a multivariate technique. Descriptive statistics such as frequency and percentage used to measure the percentage of returned questionnaire and also used to describe the respondents' profile such as their gender, educational background, their academic qualifications, and job title. Correlation and multiple regressions used for inferential statistics. The Pearson correlation used to measure the significance of linear bivariate between the independent and dependent variables thereby achieving the objective of this study. Multiple regressions used to determine the relationship between independent and dependent variables, the direction of the relationship, the degree of the relationship and strength of the relationship. This thesis found that job satisfaction has a negative influence on turnover intentions. The non significance relationship found between organizational commitment and turnover intentions.